Engineering diabetic human skin equivalent for in vitro and in vivo applications - Abedin-Do, Atieh; Zhang, Ze; Douville, Yvan; Méthot, Mirelle; Bernatchez, Julien; Rouabhia, Mahmoud (Frontiers in Bioengineering and Biotechnology, 2022)
The prevalence of diabetes is increasing worldwide. Diabetes contributes to 70% of all non-traumatic lower-limb amputations, which are directly caused by diabetic foot ulcers (DFU) that are difficult to heal. Non-healing diabetic ulcers represent one of modern society's most difficult medical challenges. One of the promising initiatives to treat DFU is the grafting of autologous skin or stimulating the skin cells at the edge of the wound to proliferate and close the wound. The present study was to engineer a diabetic human skin equivalent (DHSE) that contains fibroblasts and keratinocytes extracted from the skin collected from diabetes. The DHSE was used to investigate whether exposure to a low-intensity electrical stimulation (ES) could promote diabetic cell behavior. The ES was generated by a direct current (DC) electric field of 20 or 40 mV/mm. We demonstrated that the fibroblasts and keratinocytes could be extracted from older diabetics, cultured, and used to engineer DHSE. Interestingly, the exposure of DHSE to ES led to a structural improvement through tissue stratification, increased Ki-67 expression, and the deposition of basement membrane proteins (laminin and type IV collagen). The DHSE exposed to ES showed a high level of keratin 5 and 14 expressions in the basal and supra-basal layers. The keratinocyte proliferation was supported by an increased secretion of keratinocyte growth factor (FGF-7). Interestingly, exposure to ES decreased the activity of metalloproteinases (MMP) 2 and 9. In conclusion, we extracted keratinocytes and fibroblasts from the skin of diabetic aged donors. These cells were used to engineer skin equivalents and demonstrate that ES can promote diabetic wound healing. This DHSE can be a promising tool for various in vitro studies to understand the wound healing mechanisms under chronic inflammatory conditions such as diabetes. The DHSE could also be used as an autologous substrate to cover the DFU permanently.